Results from 99 seawater RO membrane autopsies. Issue 1 (1st October 2013) - Chesters, S P; Pena, N; Gallego, S; Fazel, M; Armstrong, M W; del Vigo, F
<x xml:space="preserve">Abstract</x> This paper presents results from ninety-nine seawater reverse osmosis (SWRO) membrane autopsies carried out by the Genesys laboratory in Madrid from 2002 and outlines the technical issues surrounding fouling and scaling of sea water membranes. The authors discuss historical results of membrane autopsies and link recent trends and changes in plant design to potential fouling and scaling issues that may result in the future. Forty per cent of autopsies showed the presence of iron, 33% clay and 21% calcium and magnesium. The principle reason for membrane failure showed 27% was due to microbiological fouling, 19% were abraded, 18% oxidized, 12% of the samples showed metal oxide present as iron, manganese and aluminium. Scale formation from calcium carbonate, calcium sulfate and silica scale accounted for 8% of the membrane failures. Only 10% of the membranes were described as clean. There has been a trend over the last decade to increase recovery rates from 30% to 40-50%. This results in a greater concentration of cations and anions and likelihood of scale formation in last position elements. The presence of suspended solids and micro-organisms causes fouling in lead elements. To counter this there is a common practice of chlorinating, acidifying and coagulating the feed water. This is done principally with the commodity chemicals, sodium hypochlorite, sulfuric acid and iron chloride coagulant. The authors conclude from the results of ninety-nine SWRO membrane autopsies that the use of these commodity chemicals can be beneficial in the pre-treatment system but also can have some serious side effects for the membranes. Suggestions for alternative strategies are made.